2011
DOI: 10.1038/mt.2011.6
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B Knockdown by AAV-delivered shRNA Lowers Plasma Cholesterol in Mice

Abstract: Serum low-density lipoprotein cholesterol (LDL-C) levels are proportionate to the risk of atherosclerotic cardiovascular disease. In order to reduce serum total cholesterol and LDL-C levels in mice, RNA interference (RNAi) was used to inhibit expression of the structural protein of LDL-C, apolipoprotein B100 (ApoB). We developed and screened 19 short hairpin RNAs (shRNAs) targeting conserved sequences in human, mouse, and macaque ApoB mRNAs (shApoB) and subsequently narrowed our focus to one candidate for in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…For instance, apolipoprotein B knockdown by a scAAV-delivered shRNA in murine liver resulted in a specific reduction of LDL cholesterol in diet-induced dyslipidemic mice, whereas high-density lipoprotein (HDL) cholesterol remained unaffected. 138 An additional option for treatment stems from retrospective profiling studies, which link aberrant microRNA expression to disease development and progression. A recent study showed that microRNA-122 inhibition by scAAV-delivered Tough Decoy RNA (a recently developed, compact, RNA polymerase III-driven microR-NA decoy) 139 lowers both HDL and LDL in healthy mice.…”
Section: Aav Gene Transfer For Hyperlipidemiamentioning
confidence: 99%
“…For instance, apolipoprotein B knockdown by a scAAV-delivered shRNA in murine liver resulted in a specific reduction of LDL cholesterol in diet-induced dyslipidemic mice, whereas high-density lipoprotein (HDL) cholesterol remained unaffected. 138 An additional option for treatment stems from retrospective profiling studies, which link aberrant microRNA expression to disease development and progression. A recent study showed that microRNA-122 inhibition by scAAV-delivered Tough Decoy RNA (a recently developed, compact, RNA polymerase III-driven microR-NA decoy) 139 lowers both HDL and LDL in healthy mice.…”
Section: Aav Gene Transfer For Hyperlipidemiamentioning
confidence: 99%
“…Previous studies showing liver toxicity with a variety of vectors carrying shRNA sequences 21–25 nucleotides also showed that shorter shRNA sequences often displayed no toxicity [17], [22]. We therefore developed a 19-mer shRNA sequence against β-gal and delivered it to ROSA26 mice using tail vein injection of 2×10 12 vg of rAAV6 (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Liverdirected ApoB siRNAs decreased total lipid levels by 70%, when the ApoB was decreased by 95% in the liver of mice [10]. Furthermore, AAV-mediated shRNA knockdown of ApoB reduced cholesterol in mice 8 weeks after a single injection of AAV-shApoB [27]. However, fat accumulation within the liver was detected [27].…”
Section: Target Genes Regulating Cholesterol Levelsmentioning
confidence: 92%
“…Furthermore, AAV-mediated shRNA knockdown of ApoB reduced cholesterol in mice 8 weeks after a single injection of AAV-shApoB [27]. However, fat accumulation within the liver was detected [27]. In nonhuman primates, ApoB siRNAs encapsulated to stable nucleic acid lipid particles (SNALPs) lowered total cholesterol levels up to 62% with 2.5 mg/kg [28].…”
Section: Target Genes Regulating Cholesterol Levelsmentioning
confidence: 96%